Uji Pupuk NPK Mutiara 16:16:16 Berbagai Jenis Mulsa terhadap Hasil Tanaman Cabai (Capsicum annum L.) - Erlida Ariani (Universitas Riau, 2009)
The research objective was to determine optimum dosage of “mutiara” NPK (16:16:16) fertilizer and various type of mulch for chili plant yield. This research was conducted at experimental plot, Faculty of Agriculture, Riau University from September 2007 until January 2008. The experimental method used was Randomized Block Design in factorial. The first factor was level of NPK fertilizer (N) namely: without NPK (N0), 125 ton/ha NPK (N1), and 250 ton/ha NPK (N2). The second factor was various organic mulch (M) namely: oil palm empty fruit bunch (TKKS) 10 ton/ha (M1), paddy chaff 10 ton/ha (M2), and hay 10 ton/ha (M3). Parameters observed were harvest time, number of fruits per plant, weight of fruits per plant, and the percentage of consumable fruits. The result showed that supplying “mutiara” NPK (16:16:16) fertilizer dosage of 250 kg/ha together with rough rice bran mulch or TKKS gave better results than other treatments.